Immunohistochemical study of hair follicle stem cells in regenerated hair follicles induced by Wnt10b - Zhang, Yiming (Int J Med Sci, 2016)
The regulation of the periodic regeneration of hair follicles is complicated. Although Wnt10b has been reported to induce hair follicle regeneration, the characteristics of induced hair follicles, especially the target cells of Wnt10b, have not yet been clearly elucidated. Thus, we systematically evaluated the expression and proliferation patterns of Wnt10b-induced hair follicles. We found that Wnt10b promoted the proliferation of hair follicle stem cells from 24 hours after AdWnt10b injection. Seventy-two hours after AdWnt10b injection, cells outside of bulge area began to proliferate. When the induced hair follicle entered full anagen, although the hair follicle stem cells were normal, canonical Wnt signaling was maintained in the hair precortex cells. Our results reveal that the target cells that overexpressed Wnt10b included hair follicle stem cells, hair precortex cells, and matrix cells.